Tourists’ Understanding of Elephant Business in Tourism Industry: A Study of International Tourists in Chiang Mai Province, Thailand - Polyapipat, Pannarai; Loh, Ph.D., Aaron (ABAC ODI JOURNAL Vision. Action. Outcome, 2015)
Abstract The elephant is the best-known national symbol of Thailand that has been linked to Thai people for centuries. However the number of elephants is declining very rapidly in the past 25 years and it is possible that the elephant could become extinct in Thailand within 10 years. As the majority of domesticated elephants are in the tourism business, then to study how tourism affects the elephant’s welfare is significant for the elephant itself, business owners and tourists. Consequently, the purpose of this research is to investigate tourists’ understanding to help in assisting business owners to operate more ethically. The survey was conducted among 382 international tourists who had visited elephant-based attractions in Chiang Mai, Thailand. The respondents were foreigners with diverse educational backgrounds and income levels. The questionaire used for the survey was based on a critical literature review, the research objectives and the hypotheses. The data collection period was from October – December 2014. The statistical analyses revealed that the trend of using animals in tourism or for entertainment has become more ethical recently. The majority of tourists participated in abusive-free activities such as observing elephants, bathing and feeding elephants, and photographing elephants. Tourists understand the ethical implications of elephant-based attractions and the expected conditions for the ethical operation of elephant-based attractions. For example, elephant-based attractions are not places where visitors should see animals entertaining them, or where elephants were abused during training. Keywords: elephant, tourism, animal ethics